An investigation into the performance and cost effectiveness of thermosyphon solar water heaters - Lee, WenShiang; Wilson, Derek R.; Michaelides, Ioannis (My University, 1992)
In this paper, the TRNSYS Simulation Program is used to investigate the monthly and annual solar fraction of a Thermosyphon Solar Water Heater and to evaluate its economic viability in terms of its life cycle savings over a conventional water heating system. The results of the simulation indicate that the yearly solar contribution of the system ranges from 63% for a high hot water consumption profile to 89% for a low consumption pattern. The payback period of the system is as low as 3 years when compared to electric water heating systems. As long as the competitor is diesel oil, the payback period increases to 7-9 years, depending on the hot water consumption profile used.
Keywords: Solar water heaters; Computer simulation; Performance